2016
DOI: 10.1016/j.bjid.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutations in HBV DNA polymerase gene associated with nucleos(t)ide resistance in treatment-naive patients with Chronic Hepatitis B in Central China

Abstract: Spontaneous HBV resistance mutations in HBV DNA polymerase were found in treatment-naive patients with CHB in Central China. These findings suggest that we should analyze HBV DNA polymerase resistance mutation associated with NAs before giving antiviral therapy such as lamivudine (LAM), adefovir (ADV), and telbivudine (LdT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…Pastor et al [15] detected rtA194T in 1 of 14 treatment-naive patients with chronic HBV infection in Strasbourg, France. In China, Zhao et al [16] detected spontaneous HBV resistance mutations other than rtA194T (such as rtM204V/I, rtL180M, rtT184G, rtS202I) in 8.9% of their treatment-naive group. In studies conducted in Turkey, Sayan et al [17] detected rtA194T mutation in 2.2% of 88 treatment-naive patients with chronic hepatitis B, while Ergünay et al [18] reported rtA194T mutation in 3.3% of 42 treatment-naive patients with chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Pastor et al [15] detected rtA194T in 1 of 14 treatment-naive patients with chronic HBV infection in Strasbourg, France. In China, Zhao et al [16] detected spontaneous HBV resistance mutations other than rtA194T (such as rtM204V/I, rtL180M, rtT184G, rtS202I) in 8.9% of their treatment-naive group. In studies conducted in Turkey, Sayan et al [17] detected rtA194T mutation in 2.2% of 88 treatment-naive patients with chronic hepatitis B, while Ergünay et al [18] reported rtA194T mutation in 3.3% of 42 treatment-naive patients with chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HBV gene resistance mutations are associated with infected HBV genotypes [8,10]. Some scholars believe that HBV C genotype is more prevalent resistant than B genotype [11,12], but some scholars have found that A181T/V mutation, ETV resistance mutation and multidrug resistance mutation is more predominant in C genotype than B genotype, The incidence of M204I and N236T mutation in B genotypes was higher than that of in C genotype [13]. Some scholars believe that the treatment responses of NAs are similar in each genotype, but there are differences among the primary resistance mutations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the patient may have some treatments with direct anti-HBV activity, however, s/he may be unaware of it. 19 There is no recommendation regarding antiviral resistance scan in naive chronic HBV treatment.…”
Section: Discussionmentioning
confidence: 99%